Clinical and molecular characteristics of carnitineacylcarnitine translocase deficiency with c.270delC and a novel c.408C>A variant - Gürbüz, Berrak Bilginer; Yılmaz, Didem Yücel; Özgül, Rıza Köksal; Koşukcu, Can; Dursun, Ali; Sivri, Hatice Serap; Coşkun, Turgay; Tokatlı, Ayşegül (The Turkish Journal of Pediatrics, 2021)
Background. Carnitine-acylcarnitine translocase deficiency (CACTD) is a rare, autosomal recessive, and highly lethal fatty acid oxidation (FAO) disorder caused by defective acylcarnitine transport across the mitochondrial membrane. CACTD is characterized by severe episodes of hypoglycemia and hyperammonemia, seizures, cardiomyopathy, liver dysfunction, severe neurological damage, and muscle weakness. Herein, we described the clinical features, biochemical, and molecular findings of three patients with CACTD, presented with poor feeding, hypoglycemia, liver dysfunctions, and hyperammonemia, but died despite intensive treatment. Cases. All cases had similar signs and symptoms like poor feeding and respiratory failure associated with liver dysfunction. Urinary organic acid profiles in the presence of hypoglycemia and hyperammonemia led us to the possible diagnosis of one of fatty acid β-oxidation defects. Results of the molecular analyses were compatible with CACTD. In addition to known mutation (c.270delC;p.Phe91Leufs*38) we detected a novel one (c.408C > A;p.Cys136*). Conclusions. All three cases died despite a very intensive therapy. Based on our experience with these three cases, it can be said that CACTD has a relatively poor prognosis, molecular studies are of most importance in suspected cases for the final diagnosis and such studies might be of help while giving genetic counselling and guidance to parents for future pregnancies.
Keywords: aclycarnitines; carnitine; carnitine acylcarnitine translocase; carnitine acyltransferases; fatty acid oxidation defects